Understanding Ziegler–Natta catalysis through your laptop - Raj, K. Vipin; Kumar, Vanka (Resonance, 2017)
This article focuses on the different components that make up Ziegler–Natta olefin polymerization systems and shows how investigating the interactions between these components through computational approaches provide crucial information about the chemistry of these systems. Hence, the necessity of theory acting as a counterpoint to experiment is revealed, underlining the importance of computational chemistry in attacking important problems of the day.